2005
DOI: 10.1158/0008-5472.can-04-4140
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Recognize Tumor-Specific Glycosylation of Carcinoembryonic Antigen on Colorectal Cancer Cells through Dendritic Cell–Specific Intercellular Adhesion Molecule-3–Grabbing Nonintegrin

Abstract: Dendritic cells play a pivotal role in the induction of antitumor immune responses. Immature dendritic cells are located intratumorally within colorectal cancer and intimately interact with tumor cells, whereas mature dendritic cells are present peripheral to the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
139
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(145 citation statements)
references
References 51 publications
(65 reference statements)
3
139
1
Order By: Relevance
“…Recently, van Gisbergen et al reported that DC-SIGN is involved in the recognition of colorectal cancer cells by DCs through the binding of Le x /Le y carbohydrates on CEA (14). The above data and our previous results (15) indicate that Le a /Le b glycans expressed on colorectal carcinoma cells are also associated with the interaction of DCs with colorectal cancer cells through DC-SIGN recognition.…”
Section: Dc-sign Mediates the Interaction Of Dcs To Primary Colorectasupporting
confidence: 77%
See 3 more Smart Citations
“…Recently, van Gisbergen et al reported that DC-SIGN is involved in the recognition of colorectal cancer cells by DCs through the binding of Le x /Le y carbohydrates on CEA (14). The above data and our previous results (15) indicate that Le a /Le b glycans expressed on colorectal carcinoma cells are also associated with the interaction of DCs with colorectal cancer cells through DC-SIGN recognition.…”
Section: Dc-sign Mediates the Interaction Of Dcs To Primary Colorectasupporting
confidence: 77%
“…Although the identification of colorectal carcinoma cell surface glycoproteins that bind to DC-SIGN was a critical step for identifying the glycoproteins involved in DC-SIGN-mediated suppression, it is important to note that colorectal carcinoma glycoproteins modified by abnormal glycans may bind to DC-SIGN and not to the regular glycans on normal colorectal cells (14). In addition, binding by DC-SIGN was specific for tumor-associated Le glycans on the colorectal carcinomas, because tumor-associated Le glycans were not observed on the HLF hepatoma.…”
Section: Dc-sign Recognizes Tumor-associated Le a /Le B Glycans Of Cementioning
confidence: 99%
See 2 more Smart Citations
“…20 The positioning of macrophages in the cutaneous tumor invasion front is not specific for CTCL in the skin because the peritumoral localization of CD209 ϩ macrophages has also been described in cutaneous melanoma. 29 The expression of CD209 has been shown to facilitate recognition of tumor antigens in colorectal cancer 30 and acute lymphoblastic leukemia T cells. 31 The up-regulation of CCL18 in MF was accompanied by increased expression of CCL17 mRNA in our MF patients.…”
Section: Discussionmentioning
confidence: 99%